Plasma lipoprotein b-amyloid in subjects with Alzheimer's disease or mild cognitive impairment - Mamo, John; Jian, Le; James, A.; Flicker, L.; Esselmann, H.; Wiltfang, J. (Royal Society of Medicine Press Ltd, 2008)
Background: Plasma amyloid -peptide (A) can compromise the blood-brain barrier, contributing to cerebrovascular alterations and amyloid angiopathy in Alzheimer's disease (AD). The objectives of this study were to investigate the distribution of lipoprotein-bound plasma-A isoforms.Methods: This involved a case-control study of subjects with AD or amnestic mild cognitive impairment (MCI) versus controls. Lipoprotein A distribution was determined in fasted plasma. For assessment of chylomicron homeostasis in the postabsorptive state, subjects were bled 4 h after a low-fat meal. The main outcome measures were plasma lipoprotein A isoform distribution and lipid homeostasis.Results: We found the majority of plasma A to be associated with triglyceride-rich lipoproteins (TRLs) encompassing chylomicrons, VLDL and IDL. For all lipoprotein groups, A1 40 was the predominant isoform, accounting for approximately 50% of the total. Thereafter, equivalent amounts of the isoforms 1 42, 2 40, 1 38, 1 37 and 1 39 were found. A1 37, A1 38 and A2 40 isoforms were significantly enriched within the TRL fraction of AD/MCI subjects and similar trends were observed for isoforms A1 39, A1 40 and A1 42. Lipoprotein-A was inversely associated with plasma total- and LDL cholesterol. AD/MCI subjects were not dyslipidaemic, however, there was evidence of accumulation of chylomicrons in the postabsorptive state.Conclusions: Our data show that A was found to be associated with plasma lipoproteins, especially those enriched with triglyceride. We find that A may be increased in normolipidaemic AD subjects, commensurate with possible disturbances in postprandial lipoprotein homeostasis.